Enhanced compatibility between a copper nanowire-based transparent electrode and a hybrid perovskite absorber by poly(ethylenimine). Issue 44 (3rd November 2017) - Hwang, Hyewon; Ahn, Jihoon; Lee, Eunsong; Kim, Kyungmi; Kwon, Hyeok-Chan; Moon, Jooho
Abstract : Poly(ethylenimine) dramatically improved compatibility between a copper nanowire electrode and a perovskite, enabling the fabrication of electrode-based perovskite solar cells with silver- and indium-free copper nanowires. Abstract : Copper nanowires (CuNWs) have been applied to hybrid perovskite solar cells (PSCs) as a window electrode. By sandwiching the CuNW network between aluminum-doped zinc oxide and adopting a poly(ethylenimine) buffer layer, the compatibility between the CuNWs and the perovskite layer could be dramatically improved. PSCs containing the CuNW-based composite electrode exhibited an average power conversion efficiency of 8.65%.